HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SD WAHDAH ISLAMIYAH ANTANG MAKASAR - Sunaryanto, Budi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2022)
Relation of Style of Headmaster Leadership of With The Performance Learn In Elementary School Wahdah Islamiyah 01 Antang Makassar of Relation of Style of Headmaster Leadership of With The Performance Learn in Elementary School Wahdah Islamiyah 01 Antang Makassar. This Research aim to to know the performance picture learn at SD Wahdah Islamiyah 01 Antang Makassardan relation among style of headmaster leadership with the performance of teacher of Elementary School Wahdah Islamiyah 01 Antang Makassar This Research represent the quantitative research While pursuant to its source, this research use the primary data that is data collected by researcher by xself / passing division kuesioner to responder in this case is teacher of at SD wahdah islamiyah 01 Antang Makassar. with the responder amount as much 36 people. Method of data collecting use the kuesioner with the scale model the likert. Data obtained to be processed with the descriptive statistical analysis. Data processing done by using SPSS version 20 Pursuant to research result indicate that the Style of headmaster leadership be at the high category with the descriptive analysis result equal to 95% and performance gurupun be at the high category with the percentage 100%. style of headmaster Leadership with the teacher performance own the very strong relation assess the value of koofisien correlation of equal to 0,823 and style applied by headmaster of at Elementary School Wahdah Islamiyah 01 Antang Makassar democratic leadership style